2020
DOI: 10.37496/rbz4920190214
|View full text |Cite
|
Sign up to set email alerts
|

Minerals and potentially toxic elements in corn silage from tropical and subtropical Brazil

Abstract: Our aim was to assess the mineral composition of corn silages produced in four states of Brazil: Goiás, Minas Gerais, Paraná, and Santa Catarina. In total, seventy-three samples were analyzed. Total element content was extracted by HNO 3 and H 2 O 2 microwave-assisted digestion, and inductively coupled plasma-mass spectrometry (ICP-MS) was used to determine concentration. Of the 31 elements analyzed (Ag,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Silage can provide up to 9% Ca, 34% K, 23% Mg, 12% P, and 15% S of respective daily needs for dairy cattle consuming 26 kg dry matter per day composed of 40% (10.4 kg DM) corn silage. For trace elements, the average corn silage can provide up to 13% Cu, 847% Fe, 80% Mn, and 11% Zn from daily intake requirements [ 110 ].…”
Section: Effect Of Nutrition On Lameness and Laminitismentioning
confidence: 99%
See 1 more Smart Citation
“…Silage can provide up to 9% Ca, 34% K, 23% Mg, 12% P, and 15% S of respective daily needs for dairy cattle consuming 26 kg dry matter per day composed of 40% (10.4 kg DM) corn silage. For trace elements, the average corn silage can provide up to 13% Cu, 847% Fe, 80% Mn, and 11% Zn from daily intake requirements [ 110 ].…”
Section: Effect Of Nutrition On Lameness and Laminitismentioning
confidence: 99%
“…Dairy cattle are estimated to require at least 22 minerals in the feed ration [109,110], 17 minerals [110]. Table 2 lists the mineral requirements for dairy cattle [111].…”
Section: Mineralsmentioning
confidence: 99%
“…In an exploratory study with 165 horses, a negative correlation was found between Zn and tensile strength [ 29 ], and the same was observed in the present study, where a relationship with a coefficient of −0.10 was obtained, and similar results were previously presented in a study on donkey hoof samples, although this was reported as hoof strength [ 30 ]. Ley did not find an association between Zn and tensile strength [ 11 ], and these findings have to be considered when feeding horses, since zinc is usually supplemented to increase the strength or quality of horse hooves. The same scenario was presented for Na, with a coefficient of −0.003, and for this reason, it is important to pay attention to the diets that are administered to horses, since an imbalance can cause abnormalities in growth and development which predispose the hoof to microfractures [ 29 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…An additional key factor is the maturity of the forage at the time of harvest [ 9 ]. Other reasons for its exclusion from diets are that its acidity is thought to adversely impact health in addition to its hygienic quality being questionable; for this reason, it is recommended that the nutritional quality of silage be characterized by sending a representative sample to the laboratory, in addition to analyzing for the possible presence of pathogenic bacteria, fungi, and mycotoxins [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these conditions also promote the proliferation of lactic acid bacteria. Anaerobiosis and a lower pH represent an unfavorable habitat for mold proliferation (Motta et al 2020).…”
Section: Introductionmentioning
confidence: 99%